SEISMIC QUIESCENCES BEFORE TWO LARGE KAMCHATKA EARTHQUAKES OF 1996 - Saltykov V.A.; Kugaenko Yu.A. (My University, 2000)
Variations in seismicity are considered in the area of two large Kamchatka earthquakes of June 21 (Mw = 7.0) and July 16, 1996 (Mw = 6.6). Both events were found to have been preceded by seismic quiescences terminating a few months before the main events. Absolute quiescences lasted as long as 14 months. The background seismicity rate decreased by a factor of four (by 75%) during 17 and 27 months for the Mw 7.0 and 6.6 events, respectively. The values of statistical significance (quantity z) were very high (above 12 and 20). The volumes around the ruptures of these earthquakes had not shown quiescences similar in duration or in significance during the entire operation time of the Kamchatka regional network. The quiescent areas only partly intersect with the rupture zones of the earthquakes. Seismicity decreases considered retrospectively in the aftershock zones are less pronounced than in the quiescent zones identified before the events.